Rural esquecido, uma oportunidade contemporânea. Transformação catalisadora para uma Quinta na Região de Marche, Itália - Giacomo Ciavattini (2021)
"Only 2% of the surface of the Earth is sitting, where 50% of the global population lives, what happens about the remaining 98%?" Rem Koolhaas, M Talks Conference, Melbourne, 2017 With this simple and alarming statistic, the Dutch architect Rem Koolhaas, OMA´s founder, has opened the door to a new field of investigation that has led him to numerous research and surprising results that have been made collected in the exhibition entitled "Countryside, the Future?" in the last year, at the Guggenheim Museum in New York. This presentation aims to actively participate in the global provocation that emerged during the exhibition, which due to the ongoing pandemic, has partially failed to get the potential attention it deserved. The countryside, this new scenario and field of investigation, has always played a marginal role in the architectural panorama of the last centuries, especially focused on the development and spread of the cities. Consequently, also the rural tradition, over the years is gradually fading. The great migration from the countryside to the city in the last century has meant that so far fewer and fewer people are interested in caring for the land, preserving it, increasing the strong caesura toward the human and nature. My research has examined a specific study area: the Marche Region, in Central Italy. This region, characterized by a strong agricultural tradition represents a good example to express the enormous potential of the diffuse rural building heritage, which thanks to new technologies and consciousness could find a chance for revival, intercepting the new economic flows dictated mostly by the tourism industry, now increasingly massive and mostly concentrated in our cities. Through the design and organization of new spaces within a local farm, the goal is to combine a new synergy between production and hospitality in the rural sphere. A new kind of multi-functionality linked to the productive spots would represent an intriguing reply to afford the very complex challenges launched by contemporaneity. Architecture and its ability to embrace various disciplines is therefore a valid instrument of synthesis with which to read and interpret the complexity that characterises this place, which has always undergone continuous transformation. The project attempts, through its evocative power, to trace a new path for the farm, thus restoring an order of measure and the right proportions that would allow to trigger potential dynamics within the rural complex, establishing above all a new strong relationship of mediation between the natural landscape and the urban reality nearby.